Diagnosis and classification in Acute Pancreatitis (Research, Society and Development, 2023)
Acute pancreatitis (AP) is a reversible inflammatory process of the pancreas and peripancreatic tissue, which can lead to the development of local edema, fatty necrosis and diffuse bleeding. The main etiologies of acute pancreatitis are alcoholic and biliary obstruction, followed by less common etiologies, such as hypertriglyceridemia, drugs, trauma and others. This systematic review aimed to clarify the diagnostic method of acute pancreatitis and to study the best diagnostic tools for predicting the severity of the disorder. The most used predictors of severity scores are the APACHE II and Ranson, however, the literature was uncertain as to the best marker. The diagnostic triad proposed by the Atlanta Classification is the most effective and accurate for determining the acute case, however it is limited by the need to wait 48 hours to complete the diagnosis of transient or permanent organ failure. It concludes that there is a need to develop new specific and sensitive predictors of severity for acute pancreatitis and the proper application of pre-existing tools in a timely manner for a timely diagnosis.